Confirming Supreme Court Justices in a Presidential Election Year - Carl Tobias (Washington University Law Review, 2017)
Justice Antonin Scalia’s death prompted United States Senate Majority Leader Mitch McConnell (R-Ky.) and Judiciary Committee Chair Chuck Grassley (R-Iowa) to argue that the President to be inaugurated on January 20, 2017—not Barack Obama—must fill the empty Scalia post. Obama in turn expressed sympathy for the Justice’s family and friends, lauded his consummate public service, and pledged to nominate a replacement “in due time,” contending that eleven months remained in his administration for confirming a worthy successor. Obama admonished that the President had a constitutional duty to nominate a superlative aspirant to the vacancy, which must not have persisted for more than one year, while the Senate had a constitutional responsibility to advise and consent on the nominee proffered. Because this dynamic affected efficacious Supreme Court operations and precipitated a constitutional standoff, the issue merits analysis. Part I surveys the Constitution’s words, policy, practical and political considerations, history, and custom. It ascertains that numerous phenomena demonstrate Obama should have recommended, and did expeditiously tap, a highly competent prospect whom the Senate ought to have promptly and carefully scrutinized. Although President Obama nominated U.S. Court of Appeals for the District of Columbia Circuit Chief Judge Merrick Garland on March 16, the upper chamber majority steadfastly refused to consider the nominee. Therefore, the piece investigates suggestions, especially for breaking the gridlock and according Judge Garland Senate review, which chamber members should have followed but did not consider.
Keywords: Supreme court; Supreme court nomination; Supreme court confirmation; Merrick Garland; Justice Garland